Implementation of Government Regulations Relating to Share Ownership of Foreign Capital: Implementasi Peraturan Pemerintah Terkait dengan Kepemilikan Saham dari Modal Asing - Emaniar Yunisavitri (Universitas Negeri Semarang, 2012)
On investment regulations, foreign investors are required to form a limited liability company whose capital consists of shares, then the government makes more specific regulations on the ownership of shares in a company established under the Foreign Investment Regulation No. 20 of 1994 as updated by Government Regulation Number 83 of 2001. This study aims to analyze ownership of shares of foreign capital which is set in both the PP. Analytical approach used is the juridical-normative approach. These results indicate that participants in the domestic investors who are not accompanied by a written arrangement that governs sanctions or granting a period of 180 days if a foreign investment company which has established and operating in Indonesia turned out after a few years can not be qualified shareholding according to Government Regulation No. 20 of 1994 Jo Government Regulation Number 83 year 2001 regarding the ownership of shares in force in Indonesia, it could create legal uncertainty for the legislation itself.